2022
DOI: 10.1111/imm.13468
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐α promotes MHC I antigen presentation of islet β cells through STAT1‐IRF7 pathway in type 1 diabetes

Abstract: Type 1 diabetes (T1D) is a T cell‐mediated autoimmune disease. Increased incidence of T1D was reported in patients receiving IFN‐α treatment. However, the exact mechanisms of IFN‐α that facilitate the pathogenesis of T1D are not fully understood. To explore the mechanism of IFN‐α on the immune system and islets, non‐obese diabetic (NOD) mice were injected with IFN‐α and the progression of autoimmune insulitis was assessed by haematoxylin and eosin (HE) staining, immunohistochemical and flow cytometry analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…It reported that phosphorylation of STAT1 increase the MHC1 antigen presentation [ 30 ]. We investigated the phosphorylation of STAT1 in cells and tumors after stimulation or treatment with STING agonist diABZI.…”
Section: Resultsmentioning
confidence: 99%
“…It reported that phosphorylation of STAT1 increase the MHC1 antigen presentation [ 30 ]. We investigated the phosphorylation of STAT1 in cells and tumors after stimulation or treatment with STING agonist diABZI.…”
Section: Resultsmentioning
confidence: 99%
“…AIP phosphorylation may be coupled to its destabilization as a mechanism to restore the inducibility of IRF7 activation and the inflammatory response. Immune homeostasis requires sufficient negative regulation to prevent autoimmune disease ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 40 , 41 ) balanced with immune activation to prevent severe and systemic infection ( 13 , 14 ).
Figure 6 Model depicting the proposed role of AIP in the suppression of IRF7 and innate antiviral signaling.
…”
Section: Discussionmentioning
confidence: 99%
“…, influenza A virus and COVID-19) ( 15 , 16 ) and autoimmune diseases. Overactivation of IRF7 has been implicated in systemic lupus erythematosus, scleroderma, and type I diabetes ( 17 , 18 , 19 ). Although the mechanisms of negative regulation of RLR signaling have been well described ( 1 , 20 , 21 , 22 , 23 ), how IRF7 is negatively regulated remains poorly understood.…”
mentioning
confidence: 99%
“…Immunofluorescence was performed on the paraffin-embedded pancreas sections. Pancreases were fixed, processed, stained and quantified as previously reported [ 22 ]. See ESM Methods for further details.…”
Section: Methodsmentioning
confidence: 99%